Radiolabelled Aptamers for Theranostic Treatment of Cancer - Umair Khalid; Chris Vi; Justin Henri; Joanna Macdonald; Peter Eu; Giovanni Mandarano; Sarah Shigdar (MDPI AG, 2018)
Cancer has a high incidence and mortality rate worldwide, which continues to grow as millions of people are diagnosed annually. Metastatic disease caused by cancer is largely responsible for the mortality rates, thus early detection of metastatic tumours can improve prognosis. However, a large number of patients will also present with micrometastasis tumours which are often missed, as conventional medical imaging modalities are unable to detect micrometastases due to the lack of specificity and sensitivity. Recent advances in radiochemistry and the development of nucleic acid based targeting molecules, have led to the development of novel agents for use in cancer diagnostics. Monoclonal antibodies may also be used, however, they have inherent issues, such as toxicity, cost, unspecified binding and their clinical use can be controversial. Aptamers are a class of single-stranded RNA or DNA ligands with high specificity, binding affinity and selectivity for a target, which makes them promising for molecular biomarker imaging. Aptamers are presented as being a superior choice over antibodies because of high binding affinity and pH stability, amongst other factors. A number of aptamers directed to cancer cell markers (breast, lung, colon, glioblastoma, melanoma) have been radiolabelled and characterised to date. Further work is ongoing to develop these for clinical applications.